Literature Review: Faktor-Faktor yang Mempengaruhi Status Gizi pada Anak Penyandang Disabilitas - Silviana Wijayanti; Fina Fauziyah; Qothrunnadaa Fajr Rooiqoh (Media Gizi Ilmiah Indonesia, 2024)
Children with disabilities are children who have limitations in one or more abilities both in terms of physical and psychological. The growth of children with disabilities is strongly influenced by parenting, eating behavior, eating patterns and food intake provided by parents. The purpose of this study was to determine the factors that affect nutritional status in children with disabilities. The method used in this research is a literature review. The search for national articles used Google Scholar. The inclusion criteria were all articles with interventions that discussed parenting, eating behavior, food intake, and nutritional status in children with disabilities with articles ranging from 2012-2023. The results obtained are parenting, nutritional status, eating behavior, diet and food intake have an influence on the nutritional status of children with disabilities, so that all factors that can affect children with disabilities must be given more attention because they have a very influential impact on children with disabilities.